PENDUGAAN EROSI TANAH DI KECAMATAN RAYA KABUPATEN SIMALUNGUN BERDASARKAN METODE USLE - Mardina Juwita Oktafia Butar Butar; Kemala Sari Lubis2 Kemala Sari Lubis2; Gantar Sitanggang2 Gantar Sitanggang2 (Universitas Sumatera Utara, 2013)
Raya is a part of the upstream Padang’s watershed that plays an important role for the watershed ecosystem to determine of hydrological cycle. The decrease of vegetation because land use and slope ranging from ramps, steep to flet in this area, tringger soil erosion problems. To determine the level of soil erosion in Raya Sub Districts of Simalungun a research conducted in April-September 2012. The research was conducted using survey method and continued with soil erosion calculation by USLE (Universal Soil Loss Equation) method. The result shows the erosion level at 30% slope with orange and weeds vegetation at a heavy level of erosion hazard criteria. And at 15,4% slope with coffe without ground cover vegetation at moderate and low level of erosion hazard criteria. Key words: soil erosion, USLE method.